PERLINDUNGAN HUKUM PENJAMIN PIHAK KETIGA DALAM PERJANJIAN KREDIT USAHA RAKYAT - Widiyah Yanti (PT. Hasba Edukasi Mandiri, 2026)
This research examines legal protection for third-party guarantors in People's Business Credit (KUR) agreements, focusing on two main issues: first, the form of legal protection for third-party guarantors over mortgage rights collateral that has been paid off; and second, the conformity of banking administrative reasons regarding the primary debtor's consent to the bank's legal obligation in returning mortgage collateral belonging to third-party guarantors. This research is normative legal research using a statutory approach, conceptual approach, and case approach. Legal materials used include primary legal materials in the form of legislation and court decisions, secondary legal materials in the form of legal literature, and tertiary legal materials. Data analysis techniques are carried out qualitatively with descriptive analytical methods. The results show that: first, legal protection for third-party guarantors over mortgage rights collateral that has been paid off in KUR agreements is realized through preventive and repressive protection. Preventive protection is carried out through the application of the accessory principle, the principle of good faith, banking prudential principles, and the provisions of POJK Number 1/POJK.07/2013. Repressive protection is provided through legal remedies of default claims, tort claims, complaints to OJK, and resolution through the Financial Sector Alternative Dispute Resolution Institution (LAPS); second, the administrative reason of requiring the primary debtor's consent or signature as a condition for returning the mortgage collateral has no valid legal basis and is contrary to the provisions of Article 18 paragraph (1) of Law Number 4 of 1996 on Mortgage Rights, which affirms that mortgage rights are extinguished by law when the guaranteed debt has been paid off. The application of such requirements constitutes unlawful retention of collateral, which has the potential to cause harm to third-party guarantors and is contrary to the prudential principle, the trust principle, and the provisions on consumer protection in the financial services sector.